Effects of Leucaena Leaf Extract as a Liquid Organic Biostimulant and Harvest Timing on Yield and Seed Quality of Sesame (Sesamum indicum) in Dryland Systems - Samanhudi Samanhudi; Elvy Carolina Pane; Hassan Bashir (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Sesame productivity and seed quality in dryland systems are often constrained by low soil fertility and inappropriate harvest timing. This study aimed to evaluate the effects of Leucaena leucocephala leaf extract applied as a liquid organic biostimulant and different harvest timings on growth, yield, seed quality, and oil content of sesame cultivated under dryland conditions. The experiment was conducted using a factorial randomized complete block design with four extract doses (0, 100, 200, and 300 mL plant⁻¹) and three harvest timings (95, 102, and 109 days after planting). Vegetative growth parameters, yield components, seed physical and physiological quality, and oil content were measured and analyzed. The results showed that increasing extract doses significantly enhanced vegetative growth, capsule formation, seed weight, and total seed yield, with the highest yield obtained at 300 mL plant⁻¹. Harvest timing strongly influenced seed physiological quality and oil accumulation. Seeds harvested at 102 days after planting exhibited the highest germination performance and oil content, whereas earlier or later harvest reduced quality attributes. A moderate extract dose (200 mL plant⁻¹) combined with harvest at 102 days optimized seed quality and oil content, while higher doses favored yield maximization. These findings indicate that synchronizing organic nutrient management with appropriate harvest timing is essential to balance yield and quality in sustainable dryland sesame production systems.